A study on bus operation performance and demand sustainability (case study : Kota Kinabalu, Sabah) - Ahmad Fauzi, Raffee (2014)
Public Transport is one of the facilities that facilitate the movement and connecting communities from a place to another place. A good public transport system need to comply with world Bank Standard and other standard or requirement that can prove it their service is can be providing best service to consumer. In Malaysia, The public transport system has always been the government attention to be improved from time to time until 2011 government carried out the plan to improve the urban public transport in Malaysia. This Study On Bus Operating Performance and Demand Sustainability was conduct at Kota Kinabalu City and involved urban public transport City Bus as the main factor to Analysis. The analysis was conduct by observation on site or terminal and also on board observation. The main observation for this study is headway, Travel Distance, Load Factor, Availability and number of passenger. This observation shown that the headway range 26-28minute,Travel Distance Per bus Per day in range 86.40 to 178.70 KM, Availability range 75% to 83.33%. Comparing between the observation result and the standard show that the service by City Bus Kota Kinabalu need to improve their service since many of that indicator or standard observed is far from word Bank standard provided.